2012
DOI: 10.1063/1.3701373
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution and breakup of slender drops in an extensional flow

Abstract: The evolution of the shape of an elongated drop embedded in an extensional flow is studied in the framework of slender body theory. The external flow has a weak but not neglected inertia. The problem is governed by three dimensionless parameters: the capillary number, the external Reynolds number, and the viscosity ratio between the drop and the external fluid, and exhibits a multiplicity of stationary shapes with only one being stable. Evolution of the drop surface from initial shapes was studied when the flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
1
11
0
3
Order By: Relevance
“…Again, the shape of the slender drop is a parabola with pointed ends (Taylor, [4] Buckmaster, [6] and Acrivos and Lo [7] ): Figure 2 shows the deformation curve, which is composed of a lower branch where 2 n 2:4 and an upper branch in which 2:4 n < 1. Recently, Favelukis et al [10] studied the evolution of such a drop and found that the breakup mechanism of the viscous slender drop in creeping flow is by indefinite elongation. Acrivos and Lo [7] performed a stability analysis on small disturbances of the steady shapes and showed that the deformation of the drop along the lower branch is stable, while the deformation in the upper branch is unstable.…”
Section: Fluid Mechanics Of Slender Dropsmentioning
confidence: 99%
See 4 more Smart Citations
“…Again, the shape of the slender drop is a parabola with pointed ends (Taylor, [4] Buckmaster, [6] and Acrivos and Lo [7] ): Figure 2 shows the deformation curve, which is composed of a lower branch where 2 n 2:4 and an upper branch in which 2:4 n < 1. Recently, Favelukis et al [10] studied the evolution of such a drop and found that the breakup mechanism of the viscous slender drop in creeping flow is by indefinite elongation. Acrivos and Lo [7] performed a stability analysis on small disturbances of the steady shapes and showed that the deformation of the drop along the lower branch is stable, while the deformation in the upper branch is unstable.…”
Section: Fluid Mechanics Of Slender Dropsmentioning
confidence: 99%
“…The solution of the problem contains several lobes depending on the values of parameter n. The first solution is obtained at 2 < n < 4, the next solution is 6 < n < 8, and so on. The recent evolution studies of Favelukis et al [10] predict that the breakup mechanism of an inviscid drop under a small amount of external inertia is by centre pinching. The lobe contains two branches separated by the bifurcation turning point in which f 1 is maximum.…”
Section: Fluid Mechanics Of Slender Dropsmentioning
confidence: 99%
See 3 more Smart Citations